Rhapsody for the Theatre. Between Dance and Cinema - Denkova, Lidia; Badiou, Alain (Sledva : NBU Journal of Humanities and Arts, 2019)
A chapter from Alain Badiou’s dialogic book (with Nicolas Truong) on the condition of theatre today, its merging borders with other arts and media and its challenged perspectives tomorrow. This philosophic pamphlet is based on a public talk given by the famous philosopher at the Avignon Theatre Festival. Translated in Bulagrian by prof. Lidia Denkova.